Missing children: risks, repeats and responses - Sidebottom, Aiden (Policing and society, 2020)
Investigating reports of missing children is a major source of demand for the police in the UK. Repeat disappearances are common, can indicate underlying vulnerabilities and have been linked with various forms of exploitation and abuse. Inspired by research on repeat victimisation, this paper examines the prevalence and temporal patterns of repeat missing episodes by children, as well as the characteristics of those involved. Using data on all missing children incidents recorded by one UK police service in 2015 (n = 3352), we find that: (a) 75% of missing incidents involving children were repeats, i.e. attributed to children who had already been reported missing in 2015; (b) a small proportion of repeatedly missing children (n = 59; 4%) accounted for almost a third of all missing children incidents (n = 952, 28%); (c) over half of all first repeat disappearances occurred within four weeks of an initial police recorded missing episode; and (d) children recorded as missing ten times or more over the one year study period were significantly more likely than those recorded missing once to be teenagers, in the care system or to have drug and/or alcohol dependencies. We conclude by discussing the implications of our findings for future research and the prevention of repeat disappearances by children.